3D-Printed models as an improvement in medical professionals' education - Jakub Jachimczyk; Piotr Homa (Kazimierz Wielki University, 2023)
Increasing usage of 3D-Printed models draws attention as a cheap alternative to traditional tools used in anatomy education and post-graduate training. Models can be self-prepared using existing DICOM files and printed on consumer-level printers using widely available materials. Prepared models benefit from high approval rate from students, multiplicity of printable structures and high detail accuracy. They can be used in wide range of medical training, for e.g., otolaryngology, neurosurgery, oncology, neuroradiology. Positive outcomes include greater eligibility for resident training, surgical planning and education, when compared to market available anatomical models. Additive manufacturing is expected to increase its presence in medical education.